2018
DOI: 10.3390/nu10050602
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis Herpetiformis: A Common Extraintestinal Manifestation of Coeliac Disease

Abstract: Dermatitis herpetiformis (DH) is a common extraintestinal manifestation of coeliac disease presenting with itchy papules and vesicles on the elbows, knees, and buttocks. Overt gastrointestinal symptoms are rare. Diagnosis of DH is easily confirmed by immunofluorescence biopsy showing pathognomonic granular immunoglobulin A (IgA) deposits in the papillary dermis. A valid hypothesis for the immunopathogenesis of DH is that it starts from latent or manifest coeliac disease in the gut and evolves into an immune co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 64 publications
0
76
1
7
Order By: Relevance
“…Interestingly, other autoantibodies may also be involved, especially in extraintestinal manifestations, such as anti-ganglioside, anti-synapsin I and anti-actin antibodies [ 18 ]. Patients with CD present either typical or atypical symptoms [ 19 ] and CD is believed to perpetuate other maladies and often presents simultaneously with other autoimmune diseases [ 20 , 21 , 22 , 23 ]. Despite the great progress in CD research, new key emerging findings suggest previously unknown features of CD pathogenesis, for example at the transcriptome level of immune cells [ 24 ].…”
Section: Gluten-related Disorders and Celiac Diseasementioning
confidence: 99%
“…Interestingly, other autoantibodies may also be involved, especially in extraintestinal manifestations, such as anti-ganglioside, anti-synapsin I and anti-actin antibodies [ 18 ]. Patients with CD present either typical or atypical symptoms [ 19 ] and CD is believed to perpetuate other maladies and often presents simultaneously with other autoimmune diseases [ 20 , 21 , 22 , 23 ]. Despite the great progress in CD research, new key emerging findings suggest previously unknown features of CD pathogenesis, for example at the transcriptome level of immune cells [ 24 ].…”
Section: Gluten-related Disorders and Celiac Diseasementioning
confidence: 99%
“…Long-term prognosis is excellent with consumption of a gluten-free diet, although clinical response is slow and most patients require dapsone initially to control rash-related symptoms. 39 Iodine ingestion may cause flares of the disease and should be discouraged.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Recent studies have shown that the incidence of dermatitis herpetiformis is decreasing in contrast to CD, which is increasing. 120 Arthralgia and non-erosive arthritis can be seen in children with CD, although is not generally appreciated in clinical practice. The incidence is reported to be around 5-10%, with knee joint being the most commonly affected, followed by hip and ankle joints.…”
Section: Groups At Increased Genetic Risk Of Coeliac Diseasementioning
confidence: 99%